Potoczne i gwarowe nazwy roślin związane z imieniem Józef .......... 291 - Kulak, Ilona (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
COLLOQUIAL AND DIALECTAL NAMES OF PLANTS RELATED TO THE NAME JÓZEFThe paper focuses on plant names connected with the personal name Józef [‘Joseph’]. Its aim is to discuss their structure, motivation, semantic relations and name-forming processes, such as derivation, pluralisation and transonymisation. The material has been excerpted, among others, from dictionaries, corpora, digitized library collections, blogs and internet forums. In total, twenty-six lexical units were collected, predominantly suffixal derivatives, pluralia tantum, as well as phrases containing sacronyms, which reflect the attachment to the Catholic religion or the veneration of images of saints. The analysis revealed that plant names associated with the anthroponym Józef and its derivatives, primarily refer to two botanical species: hyssop and white lily.